Kompetensi pengetahuan, keterampilan, Motivasi Kerja, Dan Kinerja Anggota DPRD - Labay, Ilyas; ', Sujianto; ', Zulkarnaini (Jurnal Kebijakan Publik, 2012)
This studyaimed to observe the effect of knowledge competencies, skill, and motivation on the performanceof Members of the Anggota Dewan Perwakilan Rakyat Daerah (DPRD) of Riau Province. Methodsof data collection research done by filling the questionnaire to obtain data in accordance with thepurposes of research, in this item in accordance with the questions at issue. Data analysis wasperformed by measuring the degree of correlation between the independent and dependentvariables, using multiple regression analysis and correlation. Results showed partially visiblepresence of a significant and positive relationship between competence, skills, and motivation onthe performance of DPRD Riau Provincial. Simultaneous hypothesis testing to prove that there isa significant and positive relationship between competence, skills and motivation to the performanceof DPRD Riau Province.